IMPLEMENTATION OF HONESTY AND RESPONSIBILITY CHARACTER EDUCATION THROUGH THE HONESTY CANTEEN PROGRAM - Misna Risti A; Rahayu Retnaningsih; Suyono (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The honesty canteen is one of the character education program initiatives in schools. This study aims to analyze the implementation of honesty and responsibility character education through the honesty canteen program. This study uses a descriptive qualitative method. Data collection was conducted through observation, in-depth interviews, and documentation studies. The sample in this study were teachers, students, and the principal of State Elementary School 2 Lumbungkerep. Data analysis used the Miles and Huberman method starting from the data collection, reduction, and presentation stages. Based on the results of the study, the honesty canteen can be implemented effectively and can foster and improve honesty and responsibility. The implication of this study is the need for synchronization between values ​​at school and rules at home to maintain the consistency of honesty and responsibility in students.